PRAGMATIC TRANSFER OF SASAK CULTURE IN ENGLISH USE BY THE THIRD SEMESTER STUDENTS OF ENGLISH DEPARTMENT AT NAHDLATUL WATHAN UNIVERSITY IN 2014/2015 ACADEMIC YEAR - Muh Hasbullah (Jurnalistrendi : Jurnal Linguistik, Sastra dan Pendidikan, 2018)
This research was conducted to find out what are the forms of pragmatic transfer of Sasak culture in English use and to explain the reasons for pragmatic transfer of Sasak culture in the use of English by the third semester students of English department. This research was used qualitative that was qualitative explanatory research and the data have got using recording, transcribe the data from them. The data were analyzed qualitative explanatory research that used many theories these are rhetoric theory, pragmatic theory, interlanguage theory and cultures theory because pragmatic transfer of Sasak culture in English use by the third semester students of English department have the hidden meaning so that the research need the semantic translation.